Performance nutrient digestibility of yankasa sheep fed dietry levels of cassava and maize composites: Performance and digestibility of yankasa sheep (Bangladesh Journal of Agriculture, 2026)
The production of Yankasa sheep serves significant socio-economic purposes and it is one of the most common, abundant, and widely distributed sheep in Nigeria. This sheep breed is unable to reach its full potential due to high feed costs and poor nutrient intake. Therefore, the effect of 82 days of feeding with dietary levels of cassava and maize composites on performance and apparent nutrient digestibility were investigated. To do this, forty, 8–10-months old Yankasa sheep were divided into five groups of eight sheep. Each group was assigned to one of the experimental diets in a completely randomized design labelled, Treatment 1 (100% maize composite), Treatment 2 (75% maize composite and 25% cassava composite), Treatment 3 (50% maize composite and 50% cassava composite), Treatment 4 (25% maize composite and 75% cassava composite) and Treatment 5 (100% cassava composite). The dry matter intake (DMI) g/d, supplement DMI, total DMI, daily weight gain, feed conversion ratio and dry matter digestibility were significantly improved (p< 0.05) in 50%MC/50%CC than those fed the other treatments. Dressing percentage and leg weights were higher in 75%MC/25%CC and 50%MC/50%CC treatments. DMI (g/kgW0.75), final body weight, total weight gain, empty weight and crude protein digestibility were better in 75%MC/25%CC, 50%MC/50%CC and 25%MC/75% CC. Combination of varying levels of maize and cassava composites in sheep diets provided nourishable diets. However, Treatment 3 (50%MC/50%CC) gave the most enhanced performance and dry matter digestibility, and is hence recommended for enhanced Yankasa sheep production.Bangladesh J. Agri. 2025, 50(2): 56-68